2022
DOI: 10.2196/34433
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Activity Assessment of Adults With Type 2 Diabetes Using Accelerometer-Based Cut Points: Scoping Review

Abstract: Background Incorporating physical activity into lifestyle routines is recommended for individuals with type 2 diabetes. Accelerometers offer a promising method for objectively measuring physical activity and for assessing interventions. However, the existing literature for accelerometer-measured physical activity among middle-aged and older adults with type 2 diabetes is lacking. Objective This study aims to identify research studies in which accelerome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…We experienced challenges with accelerometry wear due to participants’ discomfort with the devices. A literature review revealed that accelerometry-measured activity for middle-aged women with chronic disease has limitations [ 44 ], such that physical activity can be underestimated or inconsistent across the life span [ 37 , 45 , 46 ]. More research is needed to establish activity assessment guidelines for older adults.…”
Section: Discussionmentioning
confidence: 99%
“…We experienced challenges with accelerometry wear due to participants’ discomfort with the devices. A literature review revealed that accelerometry-measured activity for middle-aged women with chronic disease has limitations [ 44 ], such that physical activity can be underestimated or inconsistent across the life span [ 37 , 45 , 46 ]. More research is needed to establish activity assessment guidelines for older adults.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of modern technology, such as accelerometers, may help overcome this barrier in the future. [ 28 ] Low levels of self-efficacy, improper goal setting, lack or inadequacy of facilities, inadequacy of family/social support, and insufficient attention to the details of cultural characteristics are other reasons. Additionally, the living environment, such as buildings, safe places to walk, and green spaces, also plays a crucial role in determining the ability and enthusiasm to be regularly active.…”
Section: Discussionmentioning
confidence: 99%
“…Troiano et al [ 16 ] counts/minute cut points were used to differentiate between light intensity (100-2,019), moderate intensity (2,020-5,998), and vigorous intensity (≥5,999). The Troiano cut points were used because they provide a relatively high threshold of moderate- and vigorous-intensity PA which makes these data fairly conservative [ 17 ]. Data were recorded at 30 Hz, and 60-second epochs were used.…”
Section: Methodsmentioning
confidence: 99%